2020
DOI: 10.21203/rs.2.9427/v6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The draft genome of horseshoe crab Tachypleus tridentatus reveals its evolutionary scenario and well-developed innate immunity

Abstract: Background: Horseshoe crabs are ancient marine arthropods with a long evolutionary history extending back approximately 450 million years, which may benefit from their innate immune systems. However, the genetic mechanisms underlying their abilities of distinguishing and defending against invading microbes are still unclear. Results: Here, we describe the 2.06 Gbp genome assembly of Tachypleus tridentatus with 24,222 predicted protein-coding genes. Comparative genomics shows that T. tridentatus and the Atlanti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Spiders and scorpions, on the other hand, possess two Hox clusters due to one round of whole‐genome duplication that occurred in their common ancestor (Schwager et al., 2017). Sequencing of the whole‐genome of T. tridentatus , a species closely related to T. gigas , showed that it contained two Hox clusters, suggesting one round of whole‐genome duplication in this lineage (Gong et al., 2019; Zhou et al., 2020). However, a recent study involving sequencing and analysis of the genome of C. rotundicauda revealed the presence of five Hox clusters (Shingate et al., 2020), which suggested at least two rounds of whole‐genome duplication.…”
Section: Resultsmentioning
confidence: 99%
“…Spiders and scorpions, on the other hand, possess two Hox clusters due to one round of whole‐genome duplication that occurred in their common ancestor (Schwager et al., 2017). Sequencing of the whole‐genome of T. tridentatus , a species closely related to T. gigas , showed that it contained two Hox clusters, suggesting one round of whole‐genome duplication in this lineage (Gong et al., 2019; Zhou et al., 2020). However, a recent study involving sequencing and analysis of the genome of C. rotundicauda revealed the presence of five Hox clusters (Shingate et al., 2020), which suggested at least two rounds of whole‐genome duplication.…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence of RDGN gene duplications in Arachnopulmonata, in tandem with improving functional genetic toolkits in P. tepidariorum (e.g., [ 107 ]), offers a unique opportunity for studying the role of sub- and neofunctionalization during the development of their eyes, and a possible role for these processes in the diversification of number, position and structure of the eyes in an ancient group of arthropods [ 32 , 34 , 93 , 97 , 98 ]. Genomic resources for mites, ticks, and harvestmen [ 108 – 110 ] reveal that apulmonate arachnid orders have not undergone the genome duplication events exhibited by Arachnopulmonata [ 41 ] and separately by horseshoe crabs [ 111 113 ]. Future comparative studies focused on understanding the ancestral role of chelicerate RDGN genes should additionally prioritize single-copy orthologs in emerging model systems independent of the arachnopulmonate gene expansion, such as the harvestman Phalangium opilio [ 53 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, genome and Hox cluster duplications are considered rare in Arthropoda [80]. Complete Hox cluster duplication in the phylum has only been reported in horseshoe crabs (Xiphosura) [34,35,81,82], and in spiders and scorpions (presumed ancestral in Arachnopulmonata). The phylogenetic placement of Amblypygi makes this group an opportune system to test the downstream prediction that P. marginemaculatus retains and expresses Hox paralogs shared by spiders and scorpions.…”
Section: Genomic Resources For Whip Spiders Corroborate Widespread Rementioning
confidence: 99%